CONCERTO FOR VIOLA AND CHAMBER ORCHESTRA BY MAIJA EINFELDE: SOME ASPECTS OF GENRE INTERPRETATION (Mūzikas akadēmijas raksti, 2024)
The Concerto for viola and chamber orchestra is the most recent symphonic composition by Maija Einfelde. It is dedicated to violist Andra Darzins, and its first performance took place on March 17, 2011 (soloist Andra Darzins, chamber orchestra Sinfonietta Rīga and conductor Normunds Šnē).